A near-surface layer heat treatment of die casting dies by means of electron-beam technology - Schuchardt, Torsten; Müller, Sebastian; Dilger, Klaus (Metals, 2021)
Increasing the service life of die casting dies is an important goal of the foundry industry. Approaches are either material-or process-related. Despite new material concepts, hot work steels such as H11 are still predominantly used in the uncoated condition for die casting dies. In order to withstand the stresses that occur, this steel is used exclusively in the quenched and tempered condition. Required properties such as high high-temperature strength and high hardness combined with high toughness are, in principle, contradictory and can only be adjusted consistently over the entire die by furnace-based heat treatment. However, the results of various investigations have shown that improvements in the thermal shock resistance and wear resistance of hot work tool steels can be achieved by thermally influencing the microstructure near the surface. Based on these studies and related findings, an approach to surface heat treatment using the electron beam was developed. Due to the particle character of the radiation and the associated possibility of high-frequency beam deflection, the electron beam offers significantly greater flexibility in energy input into the workpiece surface compared with lasers or induction. The overall technological concept envisages replacing furnace-based heat treatment in the production of casting dies by localized and demand-oriented boundary layer heat treatment with the electron beam. The experiments include, on the one hand, the experimental determination of a suitable temperature–time interval with a focus on short-term austenitization. On the other hand, a simulation-based approach of boundary layer heat treatment with validation of a suitable heat source is investigated. Regarding short-term austenitization, the corresponding temperature and time range could be narrowed down more precisely. Some of these parameter combinations seem to be very suitable for practical use. The test specimens show a hard surface layer with a depth of at least up to 6 mm and a very tough buffer layer. Numerical simulation is used to estimate the resulting metallurgical microstructure and the achievable hardness as a function of the temperature–time interval. In addition, the results provided show the possibility of determining and optimizing the material properties by means of a simulation-based approach within the framework of a purely digital process planning and subsequently transferring them into a process planning. In the technical implementation, a temperature control was first established by means of a two-color pyrometer. In the further course of research, the pyrometer will be supplemented by an internally installed infrared camera, which will allow the reproducible setting of specified temperature profiles even for complex, large-area contours in the future.
CRIS-Team Scopus Importer:2021-08-13
Keywords: Die casting; Electron beam; Heat treatment; Hot work tool steel; Near-surface layer; Simulation

An Initial Study of Ultra High Performance Concrete as Reusable Mold Material for Aluminum Casting - Link, Janna; Teichmann, Fabian; Wetzel, Alexander; Müller, Sebastian; Middendorf, Bernhard (Materials, 2025)
The initial investigation evaluates the feasibility of ultra high performance concrete (UHPC) as a material for reusable molds in aluminum casting. Two specific UHPC formulations were investigated: one based on ordinary Portland cement (OPC) and another utilizing alkali-activated materials (AAM). The study focused on investigating the surface through roughness measurements and the thermal durability through repeated casting cycles. The thermal stability of the molds was investigated by thermogravimetric analysis, mercury intrusion porosimetry, crack segmentation, optical microscopy, and electron microscopy. Results indicate that molds fabricated from AAM-UHPC exhibit relatively better performance in terms of maintaining structural integrity and surface quality over repeated uses. AAM-UHPC molds were able to withstand up to ten casting cycles with acceptable surface degradation and no significant failure, while OPC-UHPC molds exhibited a faster degradation under similar conditions. Microstructural changes and the interaction of UHPC materials with molten aluminum were investigated, highlighting the low adhesion and defect formation. Additionally, the molds demonstrated sound casting quality, with a grain size comparable to that achieved using traditional steel molds ( 90 µm), underscoring the potential of UHPC materials for enhancing casting quality and efficiency. The study concludes that UHPC, particularly with alkali-activated formulations, shows promise for low-pressure casting environment
Keywords: reusable mold casting; UHPC; surface characterization; aluminum; alkali-activated materials; die soldering

A Novel Manufacturing Method for Microwave Components by Lost Wax Casting - Panusch, David; Pelchen, Lucas; Müller, Sebastian; Gold, Gerald (IEEE Access, 2023)
A novel manufacturing strategy for the detailed fabrication of complex and mechanically robust microwave components is presented. Additive printing of the full wax positive model with a multijet printer allows free shaping on the one hand, while metal casting provides mechanical stability for a variety of applications on the other. In addition to that a slotted waveguide model is used to improve the post-processing and performance. This combination is used with a rectangular waveguide for the E-band to demonstrate the performance of this manufacturing method at higher frequencies than previous publications. Measurements on the samples show comparable attenuation coefficients to the milled split-block counterpart, i.e., less than 5 dB/m, a good root mean square (RMS) surface roughness of the inner surfaces with S q = 5.85 μm and astonishingly fine tolerances of 8.8±40.3 μm overall. Comparisons are also made between other published additive manufacturing processes.<br
Keywords: Optical waveguides Casting Attenuation Metals Surface waves Microwave theory and techniques Surface treatment Three-dimensional printing

A Reusable Concrete Mold for Light-Metal Casting - Link, Janna; Wetzel, Alexander; Schwab, Johannes; Müller, Sebastian (HiPerMat 2024 6th International Symposium on Ultra-High Performance Concrete and High Performance Building Materials for Sustainable Construction Kassel, Germany, 2024)

High performance lightweight concrete based on alkali activated slag as aluminium casting mold - Wetzel, Alexander; Link, Janna; Pelchen, Lucas; Müller, Sebastian; Middendorf, Bernhard (8th international Slag Valorisation Symposium, 18-20 April 2023, Mechelen, Belgium, 2023)

Investigations on Dual Laser Beam Welding of Aluminium High Pressure Die Castings at Reduced Ambient Pressure (403) (Peer Reviewed) - Teichmann, Fabian; Müller, Sebastian; Dilger, Klaus (ICALEO 2018, 2018)

Investigations on dual laser beam welding of aluminum high pressure die castings at reduced ambient pressure - Teichmann, Fabian; Müller, Sebastian; Dilger, Klaus (Journal of Laser Applications, 2018)
During the manufacture of aluminum high pressure die castings, the aluminum alloy is in a liquid phase during the majority of process steps. Due to the high solubility of hydrogen in liquid aluminum, the die casted part likely has an increased hydrogen content, which affects the weldability negatively. When welding these materials, hydrides dissociate and hydrogen is liberated and forms porosity during solidification. To avoid the described formation of porosity, friction stir welding below the melting point and electron beam welding with high frequency beam oscillation were investigated in prior research. Other studies reported that the formation of porosity during laser beam welding of pure aluminum was prevented by the application of dual beam configurations. However, it is well known that laser beam welding under vacuum condition has several advantages, such as the increase in penetration depth, the enhanced degasification, or the overall calming effect on the melt pool when welding ferrous metals. Aiming to combine these advantages, the current work consequently focuses on the occurrence of porosity during dual laser beam welding of aluminum die castings under vacuum (100–0.1 hPa) and atmospheric conditions. All results are based on the outcome of x-ray computed tomography or tensile testing.
Keywords: aluminium alloys; aluminium alloys; computerised tomography; die casting; laser beam welding; oscillations; tensile testing; computerised tomography; die casting; laser beam welding; oscillations; tensile testing

Laser beam welding of highly ductile secondary HPDC Aluminium Alloy at reduced ambient pressure - Teichmann, Fabian; Müller, Sebastian; Börner, Christian; Pries, Helge; Dilger, Klaus (METALL ITAL, 2016)
Keywords: Aluminium-Druckguss; Druckguss; Laserstrahlschweißen; Unterdruck; Vakuum

On the occurrence of weld bead porosity during laser vacuum welding of high pressure aluminium die castings - Teichmann, Fabian; Müller, Sebastian; Dilger, Klaus (Procedia CIRP, 2018)
Procedia CIRP, 74 (2018) 438-441. doi:10.1016/j.procir.2018.08.163
Keywords: Aluminium; Aluminium die castings; Laser vacuum welding; Laser Welding; Porosity; X-ray computed tomography

(untitled) - Teichmann, Fabian; Müller, Sebastian; Pries, Helge; Dilger, Klaus (Zbornik povzetkov referatov 56. mednarodnega livarskega posvetovanja, Portorož)

The Costs of More Sustainable Castings Can we Afford the Change? - Pelchen, Lucas; Müller, Sebastian (Lecture Notes in Mechanical Engineering, 2023)
Rising costs for fossil fuels and the need to reduce emissions in the production of castings are subjecting foundries worldwide to increasing pressure to act and innovate. Due to fierce global competition in this sector and high investment costs for alternative technologies, foundries are therefore under high pressure to transform, while at the same time having limited financial resources. This article examines the economic and environmental differences between a conventional industrial foundry process chain, a process chain based on a hydrogen (H2)-fired melting furnace and an all-electric approach using conversion of H2 to electricity within a solid oxide fuel cell. To ensure an unbiased comparison of the process chains introduced, the respective mass efficiencies are first determined using an absorbing Markov chain before calculating the mass-specific costs and emissions of each approach using a literature-based process model. The comparison of the setups shows negligible differences in terms of material loss and cost in the respective best case. However, significantly higher emission minimums are found for both H2 approaches compared to the biogas-based conventional approach, especially for the use of green H2. In summary, no significant economic disadvantages of the H2-based approaches can be identified. Even considering that the economic comparison is biased in favor of biogas due to accounting measures, the environmental difference is comparatively small. The results indicate that the conversion of the foundry industry towards more sustainable H2-based foundry process chains is in principle reasonable as well as affordable and should therefore be achieved in the medium term.
CRIS-Team Scopus Importer:2023-07-07
Keywords: absorbing Markov chain; energy demands; greenhouse gas emissions; High pressure die casting; hydrogen in foundries

The influence of ambient pressure during laser beam welding of aluminium high pressure die castings on the occurrence of weld bead porosity - Teichmann, Fabian; Müller, Sebastian; Dilger, Klaus (Lasers in Manufacturing 2017, 2017)

Thermo-Mechanical Optimization of Die Casting Molds Using Topology Optimization and Numerical Simulations - Djabraian, Serouj; Teichmann, Fabian; Müller, Sebastian (Materials, 2024)
Conventional cooling channels used in die casting molds exhibit significant drawbacks, resulting in extended cooling times for cast parts. Issues such as the formation of dirt, limescale, and corrosion substantially diminish the thermal efficiency of these channels, leading to challenges in achieving uniform cooling and potential quality issues. In response to these challenges, this study proposes Topology Optimization as a novel approach. It involves designing cooling structures through Topology Optimization to replace traditional cooling channels, incorporating both Discrete and Gaussian boundary conditions to optimize thermal efficiency. Additionally, Structural Topology Optimization is employed to ensure structural integrity, preventing deformation or yielding under high loads during the die casting process. Numerical analysis revealed superior thermal performance compared to conventional channels, particularly when subjected to Discrete and Gaussian boundary conditions. Furthermore, the application of the latter establishes conformal cooling and minimizes temperature gradients in the casting, reducing casting defects such as shrinkage porosity. These findings highlight the efficacy of Topology Optimization in addressing the challenges of traditional cooling methods, with wide-ranging implications for manufacturing processes utilizing permanent molds for shaping materials.
CRIS-Team Scopus Importer:2024-05-24
Keywords: COMSOL multiphysics; cooling structures; die casting; heat sink; mold; structural optimization; thermal optimization; topology optimization

Ultra‐high performance alkali‐activated slag as a reusable mold for light metal casting - Link, Janna; Wetzel, Alexander; Müller, Sebastian; Middendorf, Bernhard (ce/papers - Proceedings in Civil Engineering, 2023)
Light metal die casting is usually performed using steel molds. However, these lead to a reduced quality of the casting due to the occurrence of metal corrosion on the surface and the incorporation of hydrogen into the casting as a result of required process chemistry. Ultra-high performance concrete based on alkali-activated slag can be used to produce mineral molds for aluminum casting. The use of reusable mineral molds not only enables the production of various thin-walled geometries. The risk of metal corrosion is eliminated and the concrete molds can withstand multiple cycles due to their thermal stability and high strength, making them potentially superior to the already common lost mineral molds.<br
Keywords: aluminum casting; alkali-activated materials; ultra-high performance concrete; thermal resistance

(untitled) - Teichmann, Fabian; Müller, Sebastian; Pries, Helge; Dilger, Klaus (DVS Congress 2016)

Verringerung der Porenbildung beim Laserstrahlschweißen von Aluminium-Druckgusslegierungen durch reduzierten Umgebungsdruck und Doppelfokustechnik - Teichmann, Fabian; Müller, Sebastian; Pries, Helge; Dilger, Klaus (Giesserei, 2017)

Verringerung der Porenbildung beim Laserstrahlschweißen von Aluminium-Druckgusslegierungen durch reduzierten Umgebungsdruck und Doppelfokustechnik - Teichmann, Fabian; Müller, Sebastian; Pries, Helge; Dilger, Klaus (Schweissen und Schneiden, 2018)

(untitled) - Teichmann, Fabian; Müller, Sebastian; Pries, Helge; Dilger, Klaus (DVS Berichte)

(untitled) - Teichmann, Fabian; Müller, Sebastian; Pries, Helge; Dilger, Klaus (Laser- und Elektronenstrahlschweißen von Aluminiumwerkstoffen)